Kinerja Guru: Perbaikan dan Evaluasi (Studi Kasus Guru SMP di Kab Bogor) (Indo-MathEdu Intellectuals Journal, 2025)
Teacher performance at the junior high school level has a significant impact on the quality of education and student achievement, but there is inequality in this achievement, especially in peripheral areas of the village. This research aims to evaluate the factors that influence teacher performance and formulate recommendations for improvement. The methodology used is qualitative research with data collection through interviews, documentation and verification, carried out in three junior high schools in Bogor Regency involving 51 teachers as samples. The research results show that teacher performance is generally good, driven by guidance and training from the school principal. However, challenges in peripheral schools need attention due to limited access to training and managerial support. It is recommended that school principals carry out problem mapping and needs analysis to improve teacher performance evenly across all regions